Mutational and transcriptional analyses of an avian pathogenic Escherichia coli ColV plasmid - Skyberg, Jerod A (BioMed Central, 2008)
BACKGROUND: Previously we described a 184-kb ColV plasmid, pAPEC-O2-ColV, that contributed to the ability of an E. coli to kill avian embryos, grow in human urine, and colonize the murine kidney. Here, the roles of several genes encoded by this plasmid in virulence were assessed using mutational and transcriptional analyses. METHODS: Genes chosen for deletion were iss, tsh, iutA, iroN, sitA, and cvaB. In addition, a 35-kb region of the plasmid, containing iss, tsh, and the ColV and iro operons, along with a 15-kb region containing both the aerobactin and sit operons, were deleted. Mutants were compared to the wild-type (APEC O2) for lethality to chick embryos and growth in human urine. Expression of the targeted genes was also assessed under these same conditions using RT-PCR RESULTS: No significant differences between the mutants and the wild-type in these phenotypic traits were detected. However, genes encoding known or predicted iron transport systems were up-regulated during growth in human urine, as compared to growth in LB broth, while iss, hlyF, and iroN were strongly up-regulated in chick embryos. CONCLUSION: While no difference was observed between the mutant strains and their wild-type parent in the phenotypic traits assayed, we reasoned that some compensatory virulence mechanism, insensitivity of the virulence assays, or other factor could have obscured changes in the virulence of the mutants. Indeed we found several of these genes to be up-regulated in human urine and/or in the chick embryo, suggesting that certain genes linked to ColV plasmids are involved in the establishment of avian extraintestinal infection.